Gambaran Kesehatan Mental Siswa SMP Perti Kota Padang - Ratih Permata Sari (RC-INSTITUT, 2021)
The purpose of this study was to describe the mental health of students at SMP Perti Padang City. This research is quantitative research with a descriptive design. The population of this study was students of SMP Perti Padang City. The research sample consisted of 60 people. The sampling technique in this study is random sampling. Data collection using the SDQ questionnaire. The analysis was performed after the SDQ screening scores were grouped to determine the frequency distribution. Based on the results of the total difficulty score obtained from SMP Perti Padang City students, the mental health of students in the normal category amounted to 27 people (45%), borderline numbered 18 people (30%), and abnormal 15 people (25%). Meanwhile, the score of the strength of the students of SMP Perti in Padang city shows that the students of SMP Perti in Padang have prosocial behavior. The biggest problem aspect of SMP Perti students is the problem of disruptive behavior. Female students had more borderline and abnormal difficulty scores than boys. It can be concluded that SMP Perti students have mental health problems with disruptive behavior.